Sustainable trade or protectionism? examining the eu's mechanism for restricting indonesian crude palm oil imports for biofuels - Hutagalung Podja Amertha; Suyani Indriastuti; Honest Doddy molasy (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study analyzes the mechanism of the European Union’s (EU) import restrictions on Crude Palm Oil (CPO) from Indonesia, implemented through the Renewable Energy Directive (RED) and the European Union Deforestation Regulation (EUDR). The main issue examined in this research is how the EU enforces non-tariff regulations affecting Indonesia’s CPO exports, particularly through environmental standards, sustainability certifications such as RSPO and ISPO, as well as due diligence and traceability systems. This study employs a qualitative descriptive method with a literature review approach, analyzing secondary data from journals, institutional reports, and relevant literature.The findings indicate that RED and EUDR policies have negatively impacted Indonesia’s palm oil sector, leading to a decline in exports to the EU, domestic oversupply causing a drop in fresh fruit bunch (FFB) prices, and significant economic consequences for small farmers. Furthermore, the strict implementation of environmental standards and certification requirements limits market access for Indonesian palm oil producers, particularly those lacking the technology and capital to meet EU requirements. This study highlights the importance of economic diplomacy strategies and technological innovations to maintain the competitiveness of Indonesian palm oil in the global market.